(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Jatropha belongs to family of Euphorbiaceae, is an alternate or commercial crop for biodiesel production. Fresh seeds of Jatropha gossypifolia were collected during summer season (April 2022) and were dried in the sunlight for 24 hours. Around 42ml of the oil was extracted from 100 gm of seeds at 210°C from dried seeds of Jatropha gossypifolia. The seed waste with Saccharomyces cerevisiae was kept for Solid State Fermentation (SSF) for one week. Ethanol with substrate and Saccharomyces cerevisiae were used for extraction of oil after one week. The Jatropha gossypifolia seed oil contains Protein, Carbohydrate, phenol, Terpenoids, steroids, Cholesterol, Quinones, flavonoids and Cardiac glycosides. The seed oil has shown little activity with Candida, Enterococcus, Pseudomonas and Staphylococcus. Antimicrobial activity was observed with Petroleum ether or Ethanol dissolved with microbial oil (50:50).The proteinases like Trypsin and Proteinase K has shown gelatin degradation indicates the proteases making positive effect with gelatin degradation and protein degrading activity. Gossypiline has shown good binding activity showing good antimicrobial activity compared with gossipidien acid, gossipifan, and n - demethylricinine based on in silico analysis.